2010
DOI: 10.4196/kjpp.2010.14.2.83
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Hydrogen Sulfide on Pacemaker Activity of Interstitial Cells of Cajal from Mouse Small Intestine

Abstract: In this study, we studied whether hydrogen sulfide (H2S) has an effect on the pacemaker activity of interstitial cells of Cajal (ICC), in the small intestine of mice. The actions of H2S on pacemaker activity were investigated using whole-cell patch-clamp technique, intracellular Ca 2+ analysis at 30 o C and RT-PCR in cultured mouse intestinal ICC. Exogenously applied sodium hydrogen sulfide (NaHS), a donor of hydrogen sulfide, caused a slight tonic inward current on pacemaker activity in ICC at low concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
5
24
0
Order By: Relevance
“…Low-dose activation of guinea-pig gastric smooth muscle may be mediated via inhibition of voltage-gated K + channels and high-dose inhibition may be mediated via K ATP channel activation (Zhao et al, 2009). In the mouse intestine, H 2 S inhibits pacemaker amplitude and frequency of interstitial cells of Cajal at high concentrations (0.5-1.0mmoll -1 ), but may slightly stimulate at low concentrations (50-100mmoll -1 ); these effects appear to be via modulation of intracellular calcium (Parajuli et al, 2010). H 2 S also stimulates proliferation of interstitial cells of Cajal (Huang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-dose activation of guinea-pig gastric smooth muscle may be mediated via inhibition of voltage-gated K + channels and high-dose inhibition may be mediated via K ATP channel activation (Zhao et al, 2009). In the mouse intestine, H 2 S inhibits pacemaker amplitude and frequency of interstitial cells of Cajal at high concentrations (0.5-1.0mmoll -1 ), but may slightly stimulate at low concentrations (50-100mmoll -1 ); these effects appear to be via modulation of intracellular calcium (Parajuli et al, 2010). H 2 S also stimulates proliferation of interstitial cells of Cajal (Huang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the responses at 100, 500 and 1000mmoll -1 (Nagao et al, 2010), the EC 50 appears to be ~500mmoll -1 . Similarly high concentrations (500mmoll -1 H 2 S) were necessary to affect pacemaker currents in interstitial cells of Cajal from mouse small intestine (Parajuli et al, 2010).…”
Section: Comparison Of H 2 S Effects In Mammals and Troutmentioning
confidence: 99%
“…Western blotting results also demonstrated that both CBS and CSE were expressed in the rat and mouse stomach, and H2S synthesis in the rat stomach was about 75 nmol/g/h [25] . CBS and CSE were also identified in the small intestine [25][26][27][28][29][30] . In the rat duodenum and jejunum, both enzymes were expressed in the neurons of myenteric plexus, but not the smooth muscle cells or the interstitial cells of Cajal (ICCs) [27,29] .…”
Section: Ynthesis Of H2s In the Gastrointestinal Tractmentioning
confidence: 99%
“…Aside from enteric neurons and smooth muscle cells, as the pacemaker cells, the interstitial cell of Cajal (ICC) may be also a target of H2S to regulate the gastrointestinal motility. Albeit no expression of CBS or CSE in ICC, exogenous H2S was shown to inhibit the pacemaker activity of ICC [30] which may be partially responsible for the H2S-induced inhibition of small intestine motility.…”
Section: In the Stomachmentioning
confidence: 99%
See 1 more Smart Citation